Winemaking and Wine Tourism in Lubuskie as a Strategy for Local Revitalisation - Jerzy Leszkowicz-Baczyński (Journal of Spatial and Organizational Dynamics, 2020)
The current paper aims to provide a theoretical and conceptual analysis of wine tourism in Lubuskie, Poland, to relate the experiences underlying the current state of the art and to formulate some guidelines for directions for future enotourism development. Lubuskie winemaking was reborn at the beginning of the present century, after half a century of the tradition remaining dormant. The redevelopment of Lubuskie winemaking has been accompanied by numerous manifestations of the development of enotourism and is noticeable in each of the examined cases below. The article is based on the author’s research, which includes quality interviews with vineyard owners who state that, in addition to wine production, wine tourism is an equally important trend in their professional lives. Lubuskie’s enotourism promotion is consistent with the patterns developed in countries with well-established wine traditions, although it is not as diverse. An important component of Lubuskie’s tourism promotion is the reference to its pre-war tradition, combined with an exposition of its material wine heritage. The recommendations for further activities in the field of enotourism are related, on the one hand, to the expansion of the vineyards’ enotourism packages and, on the other hand, to the implementation of new concepts for the popularization of Zielona Góra’s wine heritage, including the development of the wine route in the city.